1970
DOI: 10.1136/bmj.4.5726.7
|View full text |Cite
|
Sign up to set email alerts
|

Membranoproliferative Glomerulonephritis and Persistent Hypocomplementaemia

Abstract: Summary: The clinical, laboratory, and histological findings of 50 patients with membranoproliferative glomerulonephritis are described. Three-quarters of the patients, who were mostly older children and young adults, presented clinically with a mixture of "nephritic" and "nephrotic" symptoms; the remaining quarter had no symptoms and were diagnosed after the discovery of proteinuria and microscopic haematuria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
1
5

Year Published

1972
1972
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(52 citation statements)
references
References 47 publications
6
40
1
5
Order By: Relevance
“…3) . Our results are in agreement with those of other authors who have reported similar survival rates with smaller numbers of cases [1-3, 5-10, 12, 13, 16], mostly including many children as well as cases with MPGN type II [1][2][3][5][6][7][8][9]12]. Only Barbiano di Belgiojoso et al [4] got more favorable results with a 70% probability of maintaining renal function after 10 years.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…3) . Our results are in agreement with those of other authors who have reported similar survival rates with smaller numbers of cases [1-3, 5-10, 12, 13, 16], mostly including many children as well as cases with MPGN type II [1][2][3][5][6][7][8][9]12]. Only Barbiano di Belgiojoso et al [4] got more favorable results with a 70% probability of maintaining renal function after 10 years.…”
Section: Discussionsupporting
confidence: 83%
“…We are not able to provide an explanation for this discrepancy with the studies of other authors who have found the nephrotic syndrome to be associated with a less favorable prognosis. In previous investigations no corre lation could be seen between the frequency and the severity of hypocomplementemia on one hand and the progression/remission of MPGN on the other [1,[4][5][6]10,12,13,16]. In a study of 40 patients Swainson et al [2], however, found a lowersurvival rate in hypocomplementemicas opposed to normocomplementemic MPGN.…”
Section: Discussionmentioning
confidence: 92%
“…is a form of chronic nephritis which has a distinctive glomerular morphology and is frequently accompanied by hypocomplementemia (1)(2)(3). The serum of most of the hypocomplementemic patients contains an abnormal anticomplementary substance which is capable of breaking down the third component of complement, C3, when the serum is added to normal human serum ( NHS)…”
Section: Introduction Membranoproliferative Glomerulonephritis (Mpgn)mentioning
confidence: 99%
“…In AGN post streptococcus the depression of C3 occurs in 2 to 8 weeks, while in MPGN C3 is low for months or years (Cameron et al, 1970). …”
Section: Resultsmentioning
confidence: 99%
“…To know which kind of complement activation is operating in our patients, 3. To look for the possibility of using this examination as a diagnostic aid in the differential diagnosis in certain kinds of glomerular disorders.…”
Section: Introductionmentioning
confidence: 99%